Trainer Instalasi Audio Three Way Pada Sound System Untuk Media Pembelajaran Sistem Audio - Miftachul Ulum; Faidatul Hasanah; Dian Neipa Purnamasari; Adi Kuriawan S; Deni Tri Laksono; Muttaqin Hardiwansyah (Universitas Darul Ulum, 2024)
In the world of education, practical activities are very important. This activity requires students to carry out observations, experiments and testing after obtaining the theories that have been taught. This addie method is used to determine the suitability of trainers with the help of a questionnaire. The research is in the form of an audio trainer system consisting of a tone control as a tone controller, with an OCL amplifier for the final connection, as well as a preamp for the initial connection, a mixer, and an output in the form of a speaker as well as troubleshooting for error simulation. Exercise book module to make it easier to use the Audio System Trainer. This test produced several data, namely the gain voltage on the preamp was 16.8 times at a frequency of 1 KHz, the audio mixer was 15.7 times at a frequency of 1 KHz and the OCL amplifier was 18.6 times at a frequency of 1 KHz. Audio System Trainer has a learning media appropriateness level of 92% according to experts and 88% according to students. This shows that this trainer can be applied in Audio Systems learning.